Robustness Study of Fractional Order PID Controller Optimized by Particle Swarm Optimization in AVR System - N. Ramesh Raju; P. Linga Reddy (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In this paper a novel design method for determining fractional order PID (PIλDµ) controller parameters of an AVR system using particle swarm optimization algorithm is presented. This paper presents how to employ the particle swarm optimization to seek efficiently the optimal parameters of PIλDµ controller. The robustness study is made for this controller against parameter variation of AVR system. This work has been simulated in MATLAB environment with FOMCON (Fractional Order Modeling and Control) tool box.The proposed PSOPIλDµ controller has superior performance and robust compared to GA tuned PIλDµ controller. The results are also compared with PSO tuned PID controller.